Reproductive toxicology studies supporting the safety of molindone, a dopamine receptor antagonist. Issue 16 (19th September 2018) - Gopalakrishnan, Gopakumar; Ganiger, Shivaputhrappa; White, Tacey E. K.; Yu, Chungping
Abstract : Background: An extended‐release molindone (a dopamine D2 and serotonin antagonist) is currently being developed as a novel treatment for impulsive aggression (IA) in patients optimally treated for ADHD. Oral Good Laboratory Practice reproductive toxicology studies (fertility and early embryonic [FEE], prenatal/postnatal [PPN], embryo‐fetal development [EFD]) were conducted with molindone HCl using International Conference on Harmonisation (ICH) S5(R2)‐compliant protocols. Methods: In the FEE study, 0, 5, 15, or 30 mg kg −1  day −1 was administered to female (2 weeks premating through implantation) and male (4 weeks premating for 57 days) rats, and fertility parameters were evaluated. In the EFD studies, rats received 0, 5, 20, or 40 mg kg −1 day −1 on gestational days (GDs) 6–17; rabbits received 0, 5, 10, or 15 mg kg −1 day −1 on GDs 6–18. Ovarian/uterine and fetal parameters were evaluated at term. In the PPN study, F0 rats received 0, 5, 20, or 40 mg kg −1 day −1 (GD6–LD21); behavior and reproduction were evaluated in F1 offspring. Results: Parental hypoactivity and reduced body weight gain occurred in all studies. In the FEE, prolonged estrous cycles and delayed mating occurred at ≥15 mg kg −1 day −1, without effects on fertility or embryonic development. No developmental toxicity occurred in F1 fetuses. In F1 pups, reduced preweaning growth was observed at 40 mg kg −1 day −1, but there were no effects on postweaning growth, behavior, or reproduction. Conclusions: Molindone was not developmentally toxic in rats or rabbits at 69X and 6X clinical exposures, confirming the reproductive safety of molindone. Changes in estrous cyclicity were related to species‐specific pharmacological effects of molindone in rodents and are not considered relevant to human risk.